Use of Facebook for the Community Services Practices course: Community of inquiry as a theoretical framework. (January 2018) - Keles, Esra
Abstract: This study examines an online learning community created on Facebook (FB) for the Community Services Practices (CSP) course at the Faculty of Education, Karadeniz Technical University. The study aims to analyze FB group shares and prospective teachers' views in order to investigate the reflections of the teaching process that took place within the Community Services Practices course. The study was carried out with prospective teachers enrolled in the Computer Education Instructional Technology (CEIT) Teacher Training program. Its implementation entailed a case study with 92 prospective teachers, and the FB group was used as one of the main elements of the course in which students shared weekly discussion topics, social activities, and community service projects for 12 weeks. In this context, data were gathered via an analysis of the learning environment screenshots from the FB group. Furthermore, quantitative data gathered through multiple-choice, as well as open-ended questions, were presented with reference to frequencies and percentages, whereas qualitative data were presented in the form of themes, codes, and quotations. The study attempted to interpret the findings through the 'Community of Inquiry' (CoI) framework. In this vein, FB's social network supported a teaching presence for both the instructors and the students and enabled them to share responsibility for the teaching process. Moreover, the communication and socialization characteristics of FB directly contributed to the social presence of the learning groups created through this media. While the practices implemented over FB contributed to increased social sensitivity and awareness among prospective teachers, low-quality shares and irrelevant discussions in the FB group had negative effects on the learning environment. Highlights: FB's social network supported a teaching presence for both instructors and students. Prospective teachers shared the responsibility for the teaching process. The communication characteristics of FB contributed to the social presence. The practices implemented over FB contributed to increased social sensitivity. Low-quality shares and irrelevant discussions in the FB group had negative effects.